2022
DOI: 10.1155/2022/5128870
|View full text |Cite
|
Sign up to set email alerts
|

Bracket Failure in Orthodontic Patients: The Incidence and the Influence of Different Factors

Abstract: Failure of brackets is a common problem in orthodontics. This affects the treatment time, cost, and compliance of the patient. This study was conducted to estimate the bracket failure rate and the related factors for the long term. Methodology. This ambidirectional cohort study included 150 nonsyndromic orthodontic patients undergoing fixed appliance therapy for the last two years. The same patients were followed for 7 months. Different variables related to bracket failure were evaluated. The available data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
28
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 30 publications
(39 reference statements)
11
28
1
1
Order By: Relevance
“…Most bracket bond failures occurred in the first 6 months after bonding. 13,14 Therefore, the follow-up period of this study was set at 6 months. The 6-month loss rate of attachments was 13.71%, similar to that pointed out by Lin et al 11 However, the loss rate was higher than the 6-month failure rate for brackets, which has been reported at 6.4% in a recent study.…”
Section: Discussionmentioning
confidence: 99%
“…Most bracket bond failures occurred in the first 6 months after bonding. 13,14 Therefore, the follow-up period of this study was set at 6 months. The 6-month loss rate of attachments was 13.71%, similar to that pointed out by Lin et al 11 However, the loss rate was higher than the 6-month failure rate for brackets, which has been reported at 6.4% in a recent study.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the adolescent patients in this study were in the critical period of further education, facing academic pressures and shortened time for free activities; they could not pay attention to their oral health management. Therefore, compliance was relatively lower than that of adult patients [ 21 ]; it was easy to ignore doctors' prescriptions and lose patience [ 22 ]. Orthodontic patients' compliance is related to their awareness of behavior change.…”
Section: Discussionmentioning
confidence: 99%
“…However, Almosa et al [ 16 ] reported that the average attachment failure rate in orthodontic treatments is 0.6–28.3%. Khan et al [ 7 ], in their study, revealed that the failure rate of brackets in the posterior region is higher than that of the anterior-region brackets. Menini et al [ 17 ] and Sukhia et al [ 18 ] stated, in their study, that the bracket failure rate was higher in mandibular teeth compared to maxillary teeth.…”
Section: Introductionmentioning
confidence: 99%
“…There are many factors that affect orthodontic bond strength. In relation to the material, the enamel etching method, bracket design, and type of adhesive agent are reported; related to teeth, the tooth type and fluorosis, are reported; and in relation to environmental factors, blood, saliva, and moisture contamination are reported [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%